Central and attributional models of student perception of teaching and their learning - Cáceres-Bauer, Roberto Daniel (2024)
Introduction: The central model of student perceptions presented, offering a general characterization of their perception and its role in the relationship between teaching, learning and context, from a socio-cognitive perspective. Also, the attributional model of student perception is presented, which is based on the central model and integrates the view of Weiner’s attributional theory. Background: The theoretical contribution made is based on the analysis of the student’s perception from the perspective of cognitive social psychology and socio-cognitive theories of motivation, and a substantive approach to construct validity. Discussion: The models presented offer a useful conceptual framework for research on the quality of teaching and learning, the development and validation of instruments, and educational evaluation.